ChemInform Abstract: Cesium‐Catalyzed Regioselective Synthesis of Trisubstituted Heteroatom Alkenes: A New Strategy for the Preparation of Functional Alkenes. Issue 36 (September 2015) - Chen, Jinyang; Tang, Zhi; Qiu, Renhua; He, Yunhua; Wang, Xie; Li, Ningbo; Yi, Haibo; Au, Chak‐Tong; Yin, Shuang‐Feng; Xu, Xinhua
Abstract A regio‐, chemo‐, and (Z)‐stereoselective synthesis of vinylic dichalcogenides is developed using the CsOH‐catalyzed three‐component coupling of terminal alkynes, diaryl disulfides, and diaryl diselenides or tellurides.